Vesicular disruption of lysosomal targeting organometallic polyarginine bioconjugates - Groß, Annika; Alborzinia, Hamed; Piantavigna, Stefania; Martin, Lisandra L.; Wölfl, Stefan; Metzler-Nolte, Nils (Metallomics, 2015)
Compounds which are able to destabilize the lysosomal membrane have been proposed as interesting candidates for targeted anticancer drugs due to the pronounced lysosomal changes in cancer cells. For this purpose, metallocene derivatives of a cell penetrating polyarginine peptide M-(Arg)9(Phe)2Lys-NH2 (where M = ferrocene carboxylate or ruthenocene carboxylate) were designed and their biological activities were investigated in detail. The ferrocenoyl- and ruthenocenoyl polyarginine bioconjugates were synthesized via Fmoc solid-phase peptide synthesis (SPPS) protocols on a microwave-assisted synthesizer. After HPLC purification >98% purity was observed for all conjugates. Their interaction with supported biomimetic membranes was investigated on a quartz crystal microbalance (QCM) and revealed a very strong binding of the metallocene peptides and their metal-free congeners to an artificial eukaryotic membrane model (DMPC-cholesterol). To demonstrate their antiproliferative utility as cytotoxic compounds for a targeted anticancer drug, cell viability (by the crystal violet assay), apoptosis (flow cytometry, Ann V/PI staining), induction of reactive oxygen species (ROS, by flow cytometry with dihydroethidium staining), and changes in cancer cell metabolism, e.g. respiration and glycolysis, were studied. Our results reveal only a weak toxicity for the metal-free polyarginine peptide, which could be significantly enhanced (to ca. 50 μM against HeLa cells in the best case) by coupling ferrocene or ruthenocene carboxylates to the N-terminus of the peptide. The investigation of the cellular uptake and intracellular localization by fluorescence microscopy revealed an enhanced vesicular disruption by the metallocene bioconjugate compared to the metal-free derivative which could be triggered by light and chemicals. Further studies of apoptosis, respiration, glycolysis and ROS formation reveal the superior characteristics of the metallocene compounds. While most cells remain viable even at 300 μM of the metal free bioconjugate 1, most cells are dead or in late stages of apoptosis at 200 μM of the ruthenocene derivative 3, and at 100 μM of the most active ferrocene derivative 2, however, all show very little sign of necrosis. Also, the metal free compound 1 does not induce ROS formation but both metallocene-polyarginine bioconjugates are clearly associated with enhanced intracellular ROS levels, with levels for the redox-active ferrocene derivative being two times higher than for the structurally very similar but redox-silent ruthenocene derivative. We propose that such metallocene-polyarginine peptides induce lysosomal membrane permeabilization and thereby could be developed towards targeted anticancer drugs.